Effect of Glyceryl Trinitrate on Hemodynamics in Acute Stroke: Data From the ENOS Trial. Issue 2 (February 2019) - Appleton, Jason P.; Woodhouse, Lisa J.; Bereczki, Daniel; Berge, Eivind; Christensen, Hanne K.; Collins, Rónán; Gommans, John; Ntaios, George; Ozturk, Serefnur; Szatmari, Szabolcs; Wardlaw, Joanna M.; Sprigg, Nikola; et al.
Abstract : Background and Purpose—: Increased blood pressure (BP), heart rate, and their derivatives (variability, pulse pressure, rate-pressure product) are associated with poor clinical outcome in acute stroke. We assessed the effects of glyceryl trinitrate (GTN) on hemodynamic parameters and these on outcome in participants in the ENOS trial (Efficacy of Nitric Oxide in Stroke). Methods—: Four thousand and eleven patients with acute stroke and raised BP were randomized within 48 hours of onset to transdermal GTN or no GTN for 7 days. Peripheral hemodynamics were measured at baseline (3 measures) and daily (2 measures) during treatment. Between-visit BP variability over days 1 to 7 (as SD) was assessed in quintiles. Functional outcome was assessed as modified Rankin Scale and cognition as telephone mini-mental state examination at day 90. Analyses were adjusted for baseline prognostic variables. Data are mean difference or odds ratios with 95% CI. Results—: Increased baseline BP (diastolic, variability), heart rate, and rate-pressure product were each associated with unfavorable functional outcome at day 90. Increased between-visit systolic BP variability was associated with an unfavourable shift in modified Rankin Scale (highest quintile adjusted odds ratio, 1.65; 95% CI, 1.37–1.99), worse cognitive scores (telephone mini-mental state examination: highest quintile adjusted mean difference, −2.03; 95% CI, −2.84 to −1.22), and increased odds of death at day 90 (highest quintile adjusted odds ratio, 1.57; 95% CI, 1.12–2.19). GTN lowered BP and rate-pressure product and increased heart rate at day 1 and reduced between-visit systolic BP variability. Conclusions—: Increased between-visit BP variability was associated with poor functional and cognitive outcomes and increased death 90 days after acute stroke. In addition to lowering BP and rate-pressure product, GTN reduced between-visit systolic BP variability. Agents that lower BP variability in acute stroke require further study. Abstract : Supplemental Digital Content is available in the text.